2012
DOI: 10.1002/cbdv.201100262
|View full text |Cite
|
Sign up to set email alerts
|

Essential‐Oil Diversity of Three Calamintha Species from Greece

Abstract: The aim of the present study was to contribute to the knowledge of the essential-oil composition of the Calamintha officinalis-nepeta complex in Greece and to clarify the main patterns of its variation. The oils obtained from 22 wild-growing populations of C. glandulosa, C. nepeta, and C. menthifolia were studied. They could be classified into two different chemotypes, which correspond to the main biosynthetic routes of the C(3)-oxygenated p-menthane compounds. Chemotype I includes oils rich in trans-piperiton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 35 publications
2
15
1
Order By: Relevance
“…Within the same population, essential oil presents differences in chemical composition due to biological activities of the plant (Eisenman, Juliani, Struwe, & Simon, 2013). This variation within the same species has been reported by several researchers (Rao, Rajput, & Mallavarapu, 2011;Karousou, Hanlidou, & Lazari, 2012;Verma, Padalia, Chauhan, & Thul, 2013).…”
Section: Introductionsupporting
confidence: 52%
“…Within the same population, essential oil presents differences in chemical composition due to biological activities of the plant (Eisenman, Juliani, Struwe, & Simon, 2013). This variation within the same species has been reported by several researchers (Rao, Rajput, & Mallavarapu, 2011;Karousou, Hanlidou, & Lazari, 2012;Verma, Padalia, Chauhan, & Thul, 2013).…”
Section: Introductionsupporting
confidence: 52%
“…The literature data clearly indicate the presence of a remarkable chemical polymorphism and great intraspecific variability. Some authors observed that the oil composition seemed to be independent of the geographical origin of the sample [ 34 , 75 ], while others reported a strong chemical variability depending on the origin of the samples [ 51 ], as well as environmental conditions on the nature of plant chemical composition [ 17 ]. Described chemotypes are diverse, but the major components in the oils generally belong to the C-3 oxygenated p -menthanes such as PUL, menthone, isomenthone, and piperitone and piperitenone with their oxides or, more rarely, C-6 oxygenated p -menthane compounds such as carvone ( Table 2 ) [ 17 , 23 ].…”
Section: Essential Oil Composition Of Cnmentioning
confidence: 99%
“…The presence of at least 46 compounds in the oil was also reported, and the major ones were found to be the two diastereoisomers of piperitone oxide (55%) and β-bisabolene (8.5%) [ 81 ]. Another study on material of Greek origin showed 41% of PUL and 32% of menthone, with piperitone (7.3%) and piperitenone (7%) as important constituents [ 82 ], while two chemotypes were noted by others [ 75 ]. The first was rich in PUL and/or menthone and/or isomenthone, and the sum of the contents of these three ketones ranged from 56.8% to 89.9%.…”
Section: Essential Oil Composition Of Cnmentioning
confidence: 99%
“…There are a lot of literature information relating to research biological activities and the essential oil extracted from the Calamintha species [Kitic et al, 2005;Alan et al, 2010;Septi et al, 2011;Regina et al, 2012]. Aforementioned species contain bioactive materials like essential oils, flavonoids, vitamin C, saponins, triterpenoide,.…”
Section: Introductionmentioning
confidence: 99%